Slow penetration for characterizing concrete for digital fabrication. (July 2022) - Reiter, Lex; Wangler, Timothy; Roussel, Nicolas; Flatt, Robert J.
Abstract: Digital fabrication processes with concrete require a specific yield stress evolution after placing. This paper shows that this goal can be achieved with displacement controlled continuous slow penetration methods, and gives a model understanding and specific suggestions for measurement. It is found that the force recorded in continuous and point-wise penetration tests with a conical tool moving at a slow rate scales linearly and over multiple decades with independent measurements of yield stress carried out using uniaxial compression and vane test. A model adapted from soil-mechanical stability predicts the bearing capacity factor that relates the penetration force to yield stress. The experimental value agrees with the predicted one for an undrained/plastic material. The measurements indicate a yield stress validity range of 1–200 kPa and as low as 0.1 kPa with consideration of depth dependency. This range is the one of greatest interest for structural build-up in digital fabrication during production.